Forças propulsoras e restritivas na implementação da logística reversa em organizações industriais: estudo de casos múltiplos em organizações brasileiras - Andrade, Regiane Passariello (2014)
Organizations and consumers understand the importance of sustainability and preservation of the environment, but the integration of processes ranging from raw materials to the final consumer is required. The distribution logistics processes, even taking into account the integration of the supply chain links are not sufficient to obtain the preservation of the environment. Thus, a new area arises that seeks not only the timing of the distribution process of the products, but mainly the treatment of post-consumer products and after sales. The objective of this work is to identify in literature the driving and restraining forces most common and relevant to the adoption of reverse logistics practices. After identifying the strengths in the literature, this paper through multiple case study will verify the existence of such forces in organizations, so that is performed the comparison between literature and reality calculated in such organizations. The results of this study demonstrate the identification of driving and restraining forces in the implementation of reverse logistics in the literature, and that according to the reference frame, are considered as per the understanding and relevance of each company studied. The driving force most cited by the authors surveyed was the relationship of reverse logistics activities with the preservation of the environment, this force also seen as a driver in all the surveyed organizations, since the restraining force most cited by the authors was the law, due to lack of understanding of some organizations on their application and sanctions. Such identification and comparison of restrictive and driving forces is the basis for that managers are aware of the possible forces involving the implementation of reverse logistics, but it is important to note that the results can not be generalized to all organizations and segments, therefore recommend the expansion of studies related to implementation of reverse logistics in organizations.